Pedestrian connectivity network linking the Pureza-PUP, Sta. Ana and Lambingan Pasig River Ferry Terminals - Gonzales, Lareina Daniella D.R (College of Architecture, University of the Philippines Diliman, 2019)
The Pasig River is 25 kilometers long with 12 stations scattered along the river. It was once described as a river that is pristine, majestic and breathtaking. It was known for being one of the most economically important rivers located in the Philippines. It was once used as a major transport route and a source of water in the Philippines. The river was also known for being a scenic location where people get to relax and enjoy. However, due to the negligence of industrial developments, the river became very polluted and was used as a dumpsite for the factories which resulted in the Pasig river to have an unbearable smell. Linear parks such as the Pasong Tamo Linear Park and Poblacion Linear Park, as well as the Maytunas Creek, Ermitano Creek and Estero de Sampaloc, were inaugurated by the PRRC to improve the riverbank's condition. However, these parks have no linkages that would connect them with each other. The author aims to design walkable spaces along the different stations on the riverside of Pasig River as well as incorporate visual linkages in order to connect the existing spaces as well as improve both aesthetic and functional values of the area using landscape architectural design approaches. The thesis will be designed in consideration of pedestrian usage to promote walkable linear parks as well as promote the rich culture of the Pasig River.